Financial Ratios Analysis Using the Camel Method to Assess Financial Performance at PT. People's Bank of Indonesia (Persero) Tbk - Nursyahidah, Sumaya; Natsir, Uhud Darmawan; Nurman; Ramli, Anwar; Budiyanti, Hety (Economics and Business Journal (ECBIS), 2023)
This study aims to measure and analyze the financial performance of PT. Bank Rakyat Indonesia Persero Tbk. The data used is secondary data and uses data collection methods, namely documentation techniques. The data used in this study is the financial report data of PT. Bank Rakyat Indonesia Persero Tbk which is reported to Bank Indonesia and has been published by the Indonesia Stock Exchange. Based on the results of the data analysis, it is concluded that CAMEL is an analysis of the soundness of a bank using the CAR ratio on capital, the KAP ratio on Asset Quality, the NPM ratio on Management, the ROA and BOPO ratios on Profitability, and the LDR ratio on Liquidity. From the results of research on financial performance and its relation to financial ratios using the CAMEL method, then it can be said that during the last four years (2017-2020) which shows that the financial performance achieved by PT. Bank Rakyat Indonesia Persero Tbk, is in the healthy category.